Grain boundary diffusion method for neodymium-iron-boron magnet through magnetic adsorption deposition and magnetic adsorption deposition equipment
Through magnetic adsorption and deposition technology, the diffusion source powder is attached to the neodymium iron bo magnet, which solves the problems of inconsistent magnet performance and low adhesion efficiency in the prior art, and realizes the mass production of high-performance and consistent neodymium iron bo magnets.
Patent Information
- Application Number
- CN202411310744.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The prior art is difficult to achieve efficient and automated diffusion source attachment during the grain boundary diffusion of neodymium iron boron magnets, resulting in inconsistent magnet performance and relying on manual operation, making it difficult to meet the large-scale supply needs of high-performance magnets.
By using magnetic adsorption and deposition, the diffusion source powder is attached to the surface of the NdFeB magnet after saturated magnetic charging and thermal demagnetization treatment through magnetic adsorption, and is subjected to diffusion heat treatment to achieve efficient grain boundary diffusion.
This method can greatly improve magnetic performance, simplify the magnetic charging process, and realize the batch preparation of high-performance and consistent diffused neodymium iron boron magnets to meet the needs of efficient batch production.
Smart Images

Figure CN119400577A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of NdFeB magnets, and relates to a grain boundary diffusion method of NdFeB magnets using magnetic adsorption deposition and a magnetic adsorption deposition device. Background Art
[0002] With the in-depth application of grain boundary diffusion technology in NdFeB permanent magnet materials, high coercivity and high performance NdFeB magnets have developed rapidly and have become an indispensable key functional material in high-tech fields such as rail transportation and new energy vehicles. The complete grain boundary diffusion technology usually includes the following process: ①Preparation of diffusion sources of specific components; ②Attaching the diffusion source to the surface of the target magnet; ③Putting the magnet with the diffusion source attached into a heat treatment furnace for diffusion heat treatment; ④Surface processing of the diffused magnet to make the final diffused magnet have a smooth and bright surface. In terms of diffusion source research and development, after long-term exploration, multi-component rare earth alloy diffusion sources with multiple elements coexisting have gradually replaced rare earth elements and their simple compounds (oxides, hydrides, fluorides). Because of their low raw material cost and good diffusion modification effect, they are considered to be the most promising diffusion source system. In order to adapt to the development and application of diffusion source systems based on multi-component rare earth alloys, the multi-component rare earth alloys are first prepared into powders and then fully mixed with organic solvents (glue) to prepare slurries, and finally the process of attaching the diffusion source by spraying and screen printing has become the mainstream. In this process, although organic solvents or glues can avoid excessive oxidation of rare earth alloy powders to a certain extent and achieve the effect of adhering the diffusion source powders to the surface of the magnet, the introduction of organic solvents will inevitably lead to an increase in impurities such as carbon and hydrogen, making it impossible for the grain boundary diffusion technology to achieve the expected performance enhancement effect.
[0003] Recent studies have shown that introducing an appropriate amount of ferromagnetic elements such as Fe and Co into the diffusion source of a multi-component rare earth alloy is beneficial to improving the defects of the diffusion interface, thereby optimizing the remanent magnetism of the magnet, and at the same time will make the multi-component rare earth alloy have a certain ferromagnetism. By using the intrinsic magnetic force of the NdFeB magnet after magnetization to adsorb the diffusion source powder with ferromagnetism (containing Fe, Co and other elements), the problem of residual diffusion impurities caused by the introduction of organic solvents or adhesives can be fundamentally avoided. However, this technical solution has strict process control for the magnetization process of the magnet. The magnetization process uses a magnetic field to perform unsaturated magnetization (pre-magnetization / pre-magnetization) on the NdFeB magnet, which requires tedious experiments and calculation of the appropriate size of the magnetization magnetic field, and the magnetization deflection angle must be strictly controlled. During magnetization, the magnetic deflection angle between the normal of the magnetization coil and the C-axis must be strictly less than 5 degrees, otherwise it will lead to uneven surface magnetic distribution and affect the final adsorption effect. Even if the remanence (external magnetic moment effect / magnetic attraction) obtained under the same magnetization magnetic field conditions is quite different, resulting in poor consistency in the amount of diffusion source powder adsorbed by batch diffusion or the final magnet diffusion performance effect. At the same time, for NdFeB magnets with different coercive forces, it is difficult to accurately set the magnetizing current parameters of the magnetizing process using a magnetizer to achieve the target surface magnetic distribution. Even NdFeB magnets prepared in the same batch have coercive force fluctuations. Magnets with slight coercive force differences will also have large differences in surface magnetic distribution after magnetization using unsaturated current magnetization, which brings difficulties to the ultimate guarantee of the consistency of the quality of the diffusion source powder adsorbed by batch magnets. In addition, the above technical solution is relatively dependent on manual operation, and the diffusion source attachment efficiency is low, which is difficult to match the current growing demand for large-scale supply of high-performance diffused NdFeB magnets.
[0004] Therefore, it is necessary to develop a grain boundary diffusion method for NdFeB magnets based on the principle of magnetic adsorption deposition and diffusion source attachment equipment, so as to realize the efficient and automated attachment of ferromagnetic diffusion sources containing elements such as Fe and Co, and to achieve the purpose of mass preparation of diffused NdFeB magnets with high coercivity performance and good consistency, which is of great significance to the development of high-performance NdFeB permanent magnet materials. Summary of the invention
[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a grain boundary diffusion method for NdFeB magnets using magnetic adsorption deposition. Through magnetic adsorption deposition, diffusion source powder is attached to the surface of the magnet to be attached which is obtained by thermal demagnetization after saturation magnetization, thereby greatly improving the magnetic properties and meeting the requirements of efficient mass production.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition includes: thermal demagnetization of the NdFeB magnets after supersaturation magnetization, and then attachment of diffusion source powder and diffusion heat treatment to obtain the NdFeB magnets after grain boundary diffusion.
[0008] Preferably, the grain boundary diffusion method of the NdFeB magnet deposited by magnetic adsorption comprises:
[0009] (1) After supersaturation magnetization, the NdFeB magnet is detachably fixed on a detachable magnet fixture to obtain a magnet group to be attached;
[0010] (2) transferring the magnet group to be attached to a magnetic adsorption deposition device, and sequentially performing thermal demagnetization, dust removal and cooling, and adhering the diffusion source powder to the magnet surface through circulating powder raising to obtain the magnet to be diffused;
[0011] (3) The diffused magnet is subjected to diffusion heat treatment to obtain a NdFeB magnet after grain boundary diffusion.
[0012] Preferably, after thermal demagnetization, the pole surface magnetism of the magnet is 800 to 1100 Gs.
[0013] More preferably, after thermal demagnetization, the magnetic field difference of the pole surfaces of the magnets of the same batch is 0 to 20 Gs.
[0014] After thermal demagnetization, the magnet forms a uniform surface magnetic distribution, and the surface magnetic strength can absorb an appropriate amount of ferromagnetic diffusion source powder.
[0015] Preferably, the NdFeB magnet is a NdFeB magnet having a coercive force performance in the range of N to AH or above.
[0016] Preferably, the NdFeB magnet is surface treated before supersaturation magnetization, and the surface treatment includes at least one of alkali washing, acid washing and sand blasting.
[0017] Preferably, the magnetizing capacitance during supersaturation magnetization is greater than 4800 μF, and the magnetizing voltage is greater than 3200V.
[0018] Preferably, the oxygen content in the magnetic adsorption deposition equipment is less than 150 ppm.
[0019] Preferably, the thermal demagnetization temperature is 200-350° C., and the time is 0.1-30 min.
[0020] More preferably, the thermal demagnetization temperature is 260-300° C. and the time is 10-15 min.
[0021] Further preferably, the thermal demagnetization temperature of the NdFeB magnet with coercive force performance in the N~M range is 260~270℃, the thermal demagnetization temperature of the NdFeB magnet with coercive force performance in the H~SH range is 270~280℃, the thermal demagnetization temperature of the NdFeB magnet with coercive force performance in the UH~EH range is 280~290℃, and the thermal demagnetization temperature of the NdFeB magnet with coercive force performance in the AH range and above is 290~300℃.
[0022] Preferably, the grain boundary diffusion method of the NdFeB magnet using magnetic adsorption deposition comprises: after supersaturation magnetization of the NdFeB magnet, thermal demagnetization at 260-300°C is performed, and then diffusion source powder is attached and diffusion heat treated to obtain the NdFeB magnet after grain boundary diffusion.
[0023] Preferably, in the cyclic powder raising process, the rolling inner cavity of the attachment chamber drives the motor unit to rotate the rolling inner cavity of the attachment chamber to drive the powder raising blades in the inner cavity of the attachment chamber to cyclically raise the diffusion source powder.
[0024] Preferably, during the attachment of the diffusion source powder, the adsorption loading amount of the diffusion source powder on the NdFeB magnet is 1 to 3 wt % of the mass of the NdFeB magnet after the attachment of the diffusion source powder.
[0025] Preferably, the diffusion source powder has an average particle size of 3 to 50 μm.
[0026] Preferably, the diffusion source powder is a ferromagnetic diffusion source powder, and its chemical formula is R1 a R2 b M1 c M2 d , wherein R1 is at least one of Pr, Nd, La, Ce, and Y, R2 is at least one of Dy, Tb, Ho, and Gd, M1 is at least one of Fe, Co, and Ni, M2 is at least one of Cu, Al, Ga, Zr, Ti, and Nb, a, b, c, and d are the atomic percentages of the corresponding components, satisfying 0≤a≤40, 20≤b≤70, 60≤a+b≤80, 20≤c≤40, 0≤d≤20, and satisfying a+b+c+d=100.
[0027] Preferably, the diffusion heat treatment includes two-stage heat treatment, and the vacuum degree is ≤10 -2 Pa; the heating rate of the first stage heat treatment is 0.1-5°C / min, the holding temperature is 880-920°C, and the holding time is 1-12h; cooled to room temperature, and the second stage heat treatment is carried out, the heating rate of the second stage heat treatment is 5-15°C / min, the holding temperature is 460-520°C, and the holding time is 1-12h.
[0028] A magnetic adsorption deposition device comprises a thermal demagnetization box, a dust removal cooling box, an attachment chamber and a transition chamber which are sequentially and hermetically connected. The magnet moves in the magnetic adsorption deposition device through a transmission group.
[0029] Preferably, the transmission group includes a detachable magnet clamp group, an upper drive motor, a lower drive motor, an upper rotating gear group, a lower rotating gear group, an upper transmission chain shaft, and a lower transmission chain shaft;
[0030] The upper and lower ends of the detachable magnet fixture group are vertically fixed on the upper and lower transmission chain shafts. The upper drive motor rotates the upper rotating gear group to drive the upper transmission chain shaft to move. The lower drive motor rotates the lower rotating gear group to drive the lower transmission chain shaft to move.
[0031] Further preferably, the output power of the upper drive motor and the lower drive motor is adjusted to drive the detachable magnet fixture to present a "left-right swing" posture, and the maximum angle difference of the two-way swing is 60°.
[0032] Further preferably, the detachable magnet clamp includes two clamp nets with clamp frames as edge wrapping, and the magnet is detachably fixed in the two clamp nets by fixing bolts, and an upper clamp joint is provided at the upper end of the clamp frame, and the upper clamp joint is connected to the upper transmission chain shaft through an upper transmission chain shaft elastic component, and a lower clamp joint is provided at the lower end of the clamp frame, and the lower clamp joint is connected to the lower transmission chain shaft through a lower transmission chain shaft elastic component.
[0033] Further preferably, the material of the detachable magnetic fixture is selected from high temperature resistant stainless steel.
[0034] Preferably, the thermal demagnetization box is connected to a first inert gas source; the dust removal cooling box is connected to a cooling gas source; and the transition chamber is connected to a second inert gas source.
[0035] More preferably, the air pressure in the thermal demagnetization box is 0.05-0.2 MPa; the air pressure in the dust removal cooling box is 0.05-0.5 MPa, and the air pressure in the transition cabin is 0.05-0.2 MPa.
[0036] More preferably, the temperature in the thermal demagnetization box is 260-300°C.
[0037] Preferably, the attachment chamber comprises an attachment chamber supporting outer box and an attachment chamber rolling inner cavity, and conical tightening ports with a taper of 10 to 45 degrees are arranged at both ends of the attachment chamber rolling inner cavity; a number of inclined attachment chamber inner cavity powder stirring blades are evenly distributed inside the attachment chamber rolling inner cavity; a closable gate of the attachment chamber outer box is arranged on the top of the attachment chamber supporting outer box, and a closable gate of the attachment chamber inner cavity is arranged on the top of the attachment chamber rolling inner cavity, and the diffusion source powder enters the attachment chamber rolling inner cavity in sequence through the closable gate of the attachment chamber outer box and the closable gate of the attachment chamber inner cavity; the attachment chamber rolling inner cavity is driven by a motor group to rotate the attachment chamber rolling inner cavity to drive the attachment chamber inner cavity powder stirring blades to circulate the diffusion source powder; the linear speed of the bottom edge of the attachment chamber inner cavity powder stirring blades is 0.1 to 5.0 m / s.
[0038] Preferably, the oxygen content in the rolling inner cavity of the attachment chamber and the transition chamber is lower than 150 ppm.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention performs thermal demagnetization on the magnet after supersaturation magnetization, so that the magnet has a non-magnetic saturation state with suitable remanence and surface magnetic distribution; on this basis, diffusion source powder is attached and diffusion heat treatment is performed, which can realize batch preparation of high-performance and high-consistency diffusion magnets.
[0041] 2. Compared with directly magnetizing the magnet to the target magnetization amount, the method of the present invention does not need to conduct tedious experiments and calculate the appropriate size of the magnetization magnetic field. It directly uses the largest possible magnetic field to magnetize the NdFeB so that the NdFeB magnet reaches the magnetic saturation state, which simplifies the magnetization process. Subsequently, the thermal demagnetization characteristics of the NdFeB permanent magnet material are used for heat treatment, so that the magnet is transformed from the magnetic saturation state to a non-magnetic saturation state with appropriate remanence (external magnetic moment action / magnetic attraction) through thermal demagnetization. In this process, since NdFeB materials with similar organizational composition have almost consistent thermal demagnetization characteristics, it only needs to design a reasonable heat treatment temperature to make batches of magnets obtain consistent and appropriate remanence (external magnetic moment action / magnetic attraction), thereby obtaining batches of consistent high-performance diffusion magnets.
[0042] 3. The present invention does not need to control the magnetization deflection angle because the negative impact of the magnetic deflection angle on the surface magnetic distribution and uniformity will be eliminated after the magnet is magnetized to saturation: in the technical magnetization process of the magnet, when the external magnetic field is large enough to reach the magnetization supersaturation state, the positive domains in the magnet, or so-called "positive magnetic moments", will be unified and uniformly turned to the magnetization direction; after removing the external magnetic field, all magnetic domains will basically be transferred to the easy magnetization direction of the magnet, that is, the "lowest energy direction", that is, the easy axis direction of the magnet. At this time, there is no uneven distribution of magnetic moments in multiple directions caused by the magnetic deflection angle. Therefore, the present invention adopts saturation magnetization first and then thermal demagnetization (thermal demagnetization can achieve uniform weakening of the magnetic moment direction), which can avoid the magnetic deflection angle problem caused by the unsaturated magnetization process. Therefore, the present invention does not need to control the magnetic deflection angle of the magnetization or technical magnetization process.
[0043] 4. The grain boundary diffusion method of the NdFeB magnet deposited by magnetic adsorption in the present invention can effectively improve the magnetic properties and meet the requirements of efficient mass production.
[0044] 5. In the present invention, the diffusion source powder is circulated in the attachment chamber and combined with the bidirectional swinging motion of the detachable magnet fixture, the diffusion source powder is evenly attached to the surface of the magnet.
[0045] 6. In the magnetic adsorption deposition device of the present invention, conical tightening ports with a taper of 10 to 45 degrees are arranged at both ends of the rolling inner cavity of the attachment chamber. The function of the ports is that the diffusion source powder lifted by the powder stirring blades in the inner cavity of the attachment chamber can slide along the inner wall of the conical tightening port and enter the bottom of the rolling inner cavity of the attachment chamber again after being scattered, which can effectively prevent the diffusion source powder from overflowing.
[0046] 7. The present invention uses magnetic adsorption deposition equipment to process magnets, thereby realizing mass production of magnets and meeting batch consistency requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a simplified diagram of the magnetic adsorption deposition device of the present invention.
[0048] Figure 2 It is a cross-sectional view of the attachment chamber in the magnetic adsorption deposition device of the present invention.
[0049] Figure 3 It is a simplified diagram of the detachable magnet fixture assembly in the magnetic adsorption deposition device of the present invention.
[0050] In the figure: 1. upper drive motor; 2. upper rotating gear set; 3. detachable magnet fixture set; 4. lower rotating gear set; 5. lower drive motor; 6. upper transmission chain shaft; 7. lower transmission chain shaft; 8. thermal demagnetization box; 9. first inert gas source; 10. dust removal cooling box; 11. cooling gas source; 12. attachment chamber support outer box; 13. attachment chamber rolling inner cavity; 14. attachment chamber inner cavity closable gate; 15. attachment chamber inner cavity powder-lifting blades; 16. attachment chamber outer box closable gate; 17. diffusion source powder; 18. induction positioning control system; 19. attachment chamber rolling inner cavity drive motor set; 20. second inert gas source; 21. transition cabin; 22. magnet; 23. fixture upper joint; 24. clamp frame; 25. fixing bolt; 26. lower transmission chain shaft elastic component; 27. upper transmission chain shaft elastic component; 28. clamp net; 29. fixture lower joint. DETAILED DESCRIPTION
[0051] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0052] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.
[0053] The magnetic adsorption deposition device of the present invention comprises a thermal demagnetization box 8, a dust removal cooling box 10, an attachment chamber, and a transition chamber 21 which are sequentially and hermetically connected; the magnet moves in the magnetic adsorption deposition device through a transmission group.
[0054] When the magnet moves in the magnetic adsorption deposition device through the transmission group, the ambient oxygen content is less than 150ppm.
[0055] The thickness of the magnet is 1 to 30 mm, ensuring that the magnet is stably fixed in the detachable magnet fixture set; the thickness of the magnet is further preferably 1 to 10 mm.
[0056] The transmission group includes a detachable magnet clamp group 3, an upper drive motor 1, a lower drive motor 5, an upper rotating gear group 2, a lower rotating gear group 4, an upper transmission chain shaft 6, and a lower transmission chain shaft 7;
[0057] The upper and lower ends of the detachable magnet clamp group 3 are vertically fixed on the upper transmission chain shaft 6 and the lower transmission chain shaft 7. The upper drive motor 1 rotates the upper rotating gear group 2 to drive the upper transmission chain shaft 6 to move. The lower drive motor 5 rotates the lower rotating gear group 4 to drive the lower transmission chain shaft 7 to move.
[0058] The output power of the upper drive motor 1 and the lower drive motor 5 is adjusted to drive the detachable magnet fixture to present a "left-right swing" posture (the maximum angle difference of the two-way swing is 60°).
[0059] The detachable magnet clamp includes two clamp nets 28 surrounded by a clamp frame 24, and the magnet 22 is detachably fixed in the two clamp nets 28 by a fixing bolt 25. A clamp upper joint 23 is provided at the upper end of the clamp frame 24, and the clamp upper joint 23 is connected to the upper transmission chain shaft 6 through an upper transmission chain shaft elastic component 27. A clamp lower joint 29 is provided at the lower end of the clamp frame 24, and the clamp lower joint 29 is connected to the lower transmission chain shaft 7 through a lower transmission chain shaft elastic component 26.
[0060] The thermal demagnetization box 8 is connected to a first inert gas source 9 ; the dust removal cooling box 10 is connected to a cooling gas source 11 ; and the transition chamber 21 is connected to a second inert gas source 20 .
[0061] The attachment chamber comprises an attachment chamber supporting outer box 12 and an attachment chamber rolling inner cavity 13. Conical tightening ports with a taper of 10 to 45 degrees are arranged at both ends of the attachment chamber rolling inner cavity 13. Several inclined attachment chamber inner cavity powder stirring blades 15 are evenly distributed inside the attachment chamber rolling inner cavity 13. A closable gate 16 for the attachment chamber outer box is arranged on the top of the attachment chamber supporting outer box, and a closable gate 14 for the attachment chamber inner cavity is arranged on the top of the attachment chamber rolling inner cavity 13. Diffusion source powder 17 enters the attachment chamber rolling inner cavity 13 through the closable gate 16 for the attachment chamber outer box and the closable gate 14 for the attachment chamber inner cavity in turn. The attachment chamber rolling inner cavity 13 is rotated by the attachment chamber rolling inner cavity driving motor group 19 to drive the attachment chamber inner cavity powder stirring blades 15 to circulate the diffusion source powder 17. The linear velocity of the bottom edge of the attachment chamber inner cavity powder stirring blades is 0.1 to 5.0 m / s.
[0062] The attachment chamber is also connected to an inductive positioning control system 18 for detecting the remaining amount of diffusion source powder and controlling the addition of supplementary diffusion source powder.
[0063] Example 1
[0064] 200 pieces of N55 (N) brand magnets with a size of 25 mm × 12 mm × 4 mm were pickled and sandblasted in turn, and then supersaturated magnetized using a magnetizer, with a magnetizing capacitor of 5200 μF and a magnetizing voltage of 3600 V. After magnetization, the magnets were detachably fixed on a detachable magnet fixture to obtain a magnet assembly to be attached;
[0065] The magnet group to be attached is placed in the transmission group and transferred to the magnetic adsorption deposition equipment. The transmission group in the magnetic adsorption deposition equipment is used to move the magnet group to be attached so that it passes through the thermal demagnetization box 8, the dust removal and cooling box 10, the attachment chamber, and the transition cabin 21 in sequence.
[0066] The transmission group includes a detachable magnet clamp group 3, an upper drive motor 1, a lower drive motor 5, an upper rotating gear group 2, a lower rotating gear group 4, an upper transmission chain shaft 6, and a lower transmission chain shaft 7; the upper and lower ends of the detachable magnet clamp group 3 are vertically fixed on the upper transmission chain shaft 6 and the lower transmission chain shaft 7, the upper drive motor 1 rotates the upper rotating gear group 2, driving the upper transmission chain shaft 6 to move, and the lower drive motor 5 rotates the lower rotating gear group 4, driving the lower transmission chain shaft 7 to move.
[0067] The thermal demagnetization box 8 is connected to a first inert gas source 9, so that the thermal demagnetization box 8 is filled with argon gas, the temperature is set to 260°C, and the magnet group to be attached stays in the thermal demagnetization box 8 for 15 minutes; then the magnet group to be attached is moved to the dust removal cooling box through the transmission group.
[0068] The dust removal cooling box 10 is connected to a cooling gas source 11 and filled with nitrogen with a nitrogen pressure of 0.1 MPa. The magnet group to be attached stays in the dust removal cooling box 10 for 5 minutes; then the magnet group to be attached is moved to the attachment chamber through the transmission group.
[0069] In the attachment chamber, the output power of the upper drive motor 1 and the lower drive motor 5 is adjusted to drive the magnet group to be attached to present a "left-right swing" posture, and the two-way swing angle difference is 0 to 60°.
[0070] The attachment chamber includes an attachment chamber support outer box 12 and an attachment chamber rolling inner cavity 13. Both ends of the attachment chamber rolling inner cavity 13 are provided with conical tightening ports with a taper of 25°. The top of the attachment chamber support outer box 12 is provided with an attachment outer box closable gate 16, and the top of the attachment chamber rolling inner cavity 13 is provided with an attachment chamber inner cavity closable gate 14. The chemical formula is Pr7Nd 23 Tb 15 Dy 15 Fe 25 Ga5Al 10The diffusion source powder 17 with (atomic ratio) enters the attachment chamber rolling cavity 13 through the closable gate 14 outside the attachment chamber and the closable gate inside the attachment chamber; several inclined attachment chamber inner cavity powder stirring blades 15 are evenly distributed inside the attachment chamber rolling cavity 13; the attachment chamber rolling cavity driving motor group 19 rotates the attachment chamber rolling cavity 13 to drive the attachment chamber inner cavity powder stirring blades 15 to circulate the diffusion source powder 17; the linear speed of the bottom edge of the attachment chamber inner cavity powder stirring blades is set to 2.0m / s.
[0071] The magnet group to be attached stays in the attachment chamber for 8 minutes, and the average adsorption load of the diffusion source powder on the surface of the magnet group to be attached is 1.5wt% of the total mass; then it moves to the transition chamber 21 to obtain the magnet group to be diffused.
[0072] The transition chamber 21 is connected to a second inert gas source 20, and the transition chamber 21 is filled with argon. The oxygen content in the rolling inner cavity of the attachment chamber and the transition chamber is 80 ppm.
[0073] The magnet group to be diffused was transferred to a vacuum heat treatment furnace through a mobile glove box filled with argon gas. The vacuum degree in the vacuum heat treatment furnace was 2.5×10 -3 Pa, the temperature was increased to 900°C at a rate of 4°C / min, and after heat preservation treatment for 8 hours, it was rapidly cooled to room temperature by air cooling, and then the temperature was increased to 500°C at a rate of 10°C / min, and after heat preservation treatment for 8 hours, it was rapidly cooled to room temperature by air cooling to obtain NdFeB magnets after grain boundary diffusion.
[0074] Ten magnets were randomly selected after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface, and the average surface magnetic intensity (absolute value) of the magnet pole surface were 852Gs, 845Gs, 848Gs, 850Gs, 850Gs, 852Gs, 847Gs, 850Gs, 855Gs, and 849Gs respectively.
[0075] Ten pieces were randomly selected from 200 NdFeB magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 1 below.
[0076] Table 1. Magnetic properties data of N55(N) original magnet and sampled magnet after grain boundary diffusion
[0077]
[0078] It can be seen from the above test data that the NdFeB magnets after grain boundary diffusion prepared by the method of this embodiment can greatly improve the coercive force while meeting the requirements of efficient batch preparation.
[0079] Example 2
[0080] Compared with Example 1, the difference is that after 200 pieces of 30mm×10mm×3.5mm 50H brand magnets are pickled and sandblasted, they are supersaturated magnetized by a magnetizer, the magnetizing capacitor is 5100μF, the magnetizing voltage is 3550V, and after magnetization, they are detachably fixed on a detachable magnet fixture to obtain a magnet group to be attached; the magnet group to be attached is placed in a transmission group and transferred to a magnetic adsorption deposition device, and the transmission group in the magnetic adsorption deposition device is used to move the magnet group to be attached, so that it passes through the thermal demagnetization box 8, the dust removal and cooling box 10, the attachment chamber, and the transition cabin 21 in sequence.
[0081] The thermal demagnetization box 8 is connected to a first inert gas source 9, so that the thermal demagnetization box 8 is filled with argon gas, the temperature is set to 270°C, and the magnet group to be attached stays in the thermal demagnetization box 8 for 15 minutes; then the magnet group to be attached is moved to the dust removal cooling box through the transmission group.
[0082] The dust removal cooling box 10 is connected to a cooling gas source 11 and filled with nitrogen gas with a nitrogen pressure of 0.2 MPa. The magnet group to be attached stays in the dust removal cooling box 10 for 5 minutes; then the magnet group to be attached is moved to the attachment chamber through the transmission group.
[0083] The chemical formula is Pr 40 Dy 25 Fe 15 Co 10 The diffusion source powder 17 of Cu5Al5 (atomic ratio) enters the attachment chamber rolling cavity 13 through the closable gate 14 outside the attachment chamber and the closable gate inside the attachment chamber; several inclined attachment chamber inner cavity powder stirring blades 15 are evenly distributed inside the attachment chamber rolling cavity 13; the attachment chamber rolling cavity driving motor group 19 rotates the attachment chamber rolling cavity 13 to drive the attachment chamber inner cavity powder stirring blades 15 to circulate the diffusion source powder 17; the linear speed of the bottom edge of the attachment chamber inner cavity powder stirring blades is set to 1.5m / s.
[0084] The magnet group to be attached stays in the attachment chamber for 8 minutes, and the average adsorption load of the diffusion source powder on the surface of the NdFeB magnet is 2.0wt% of the total mass; then it moves to the transition chamber 21 to obtain the magnet group to be diffused. The transition chamber 21 is connected to a second inert gas source 20, and the transition chamber 21 is filled with argon. The oxygen content of the rolling inner cavity of the attachment chamber and the transition chamber is 80ppm.
[0085] The magnet group to be diffused was transferred to a vacuum heat treatment furnace through a mobile glove box filled with argon. The vacuum degree in the vacuum heat treatment furnace was 2.5×10 -3 Pa, the temperature was increased to 900°C at a rate of 4°C / min, and after heat preservation treatment for 8 hours, it was rapidly cooled to room temperature by air cooling, and then the temperature was increased to 500°C at a rate of 10°C / min, and after heat preservation treatment for 8 hours, it was rapidly cooled to room temperature by air cooling to obtain NdFeB magnets after grain boundary diffusion.
[0086] Ten magnets were randomly selected after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface, and the average surface magnetic intensity (absolute value) of the magnet pole surface were: 919Gs, 912Gs, 916Gs, 917Gs, 912Gs, 915Gs, 919Gs, 915Gs, 917Gs, and 912Gs.
[0087] Ten pieces were randomly selected from 200 NdFeB magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 2 below.
[0088] Table 2. Magnetic properties of 50H original magnets and sampled magnets after grain boundary diffusion
[0089]
[0090] It can be seen from the above test data that the NdFeB magnets after grain boundary diffusion prepared by the method of this embodiment can greatly improve the coercive force while meeting the requirements of efficient batch preparation.
[0091] Comparative Example 1
[0092] 200 pieces of N55 (N) brand magnets with a size of 25mm×12mm×4mm were acid-washed and sandblasted in sequence. Then, according to the surface magnetic distribution of the magnets and the test of the optimal ferromagnetic powder adsorption, the surface magnetic size required when the average adsorption load of the diffusion source powder is 2%, as well as the external magnetic field or magnetizer parameter conditions required to obtain the surface magnetic were determined; the magnetizer was used to perform unsaturated magnetization on the magnets, and the magnetization capacitor was selected to be 2000μF, the magnetization voltage was 1000V, and the magnetization deflection angle was controlled to be less than 5 degrees to obtain the magnet to be attached. The magnetized magnets were buried in a Pr7Nd 23 Tb 10 Dy 20 Fe 25 Ga5Al 10 The diffusion source powder is completely adsorbed on the surface of the magnet after magnetization, and then taken out to obtain the magnet to be diffused. The magnet to be diffused is transferred to a vacuum heat treatment furnace under argon protection and the vacuum degree is 2.5×10 -3 Under Pa conditions, the temperature was increased to 900°C at a rate of 4°C / min, and after being kept warm for 8 hours, it was rapidly cooled to room temperature by air cooling. Subsequently, the temperature was increased to 500°C at a rate of 10°C / min, and after being kept warm for 8 hours, it was rapidly cooled to room temperature by air cooling to obtain the final target diffusion magnet.
[0093] Ten magnets were randomly selected from the unsaturated magnetized magnets for surface magnetic distribution test on the pole surface. The average surface magnetic intensities (absolute values) of the pole surfaces were 821Gs, 869Gs, 807Gs, 791Gs, 847Gs, 801Gs, 833Gs, 815Gs, 850Gs, and 816Gs, respectively.
[0094] Ten magnets were randomly selected from 200 magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 3 below.
[0095] Table 3. Magnetic properties of N55 (N) original magnet and sampled magnet after conventional magnetic adsorption diffusion
[0096]
[0097] It can be seen from the above test data that, compared with the method in Example 1, the magnetic properties of the magnets after traditional magnetic adsorption diffusion in this comparative example fluctuate greatly (the Hcj of the same batch of magnets differs by 1.93), which cannot meet the strict batch consistency requirements.
[0098] Comparative Example 2
[0099] Compared with Example 1, the difference is that the temperature inside the thermal demagnetization box is 305°C.
[0100] Ten magnets were randomly selected after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface, and the average surface magnetic intensity (absolute value) of the magnet pole surface were: 329Gs, 335Gs, 332Gs, 327Gs, 341Gs, 335Gs, 329Gs, 339Gs, 337Gs, 329Gs.
[0101] Ten magnets were randomly selected from 200 magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 4.
[0102] Table 4. Magnetic properties data of N55(N) original magnet and sampled magnet after grain boundary diffusion
[0103]
[0104] It can be seen from the above test data that when the thermal demagnetization temperature is set higher than the parameter range of the present invention, the coercive force of the obtained magnet after grain boundary diffusion is significantly reduced, and the consistency of magnetic properties becomes worse.
[0105] This is because when the thermal demagnetization temperature is higher than the temperature range of the technical solution of the present invention, the magnetic moment or surface magnetism of the magnet disappears too much, and the surface magnetic strength of the magnet is less than the strength required for magnetic adsorption of an appropriate amount of diffusion source powder. Therefore, the adsorbed powder becomes too little or uneven, resulting in a worse final diffusion amplification effect.
[0106] Comparative Example 3
[0107] Compared with Example 1, the difference is that the temperature inside the thermal demagnetization box is 250°C.
[0108] Ten magnets were randomly selected from 200 magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 5.
[0109] Ten magnets were randomly selected from the magnets after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface. The average surface magnetic intensity (absolute value) of the magnet pole surface were: 1875Gs, 1853Gs, 1912Gs, 1897Gs, 1905Gs, 1897Gs, 1882Gs, 1932Gs, 1869Gs, and 1892Gs.
[0110] Table 5. Magnetic properties data of N55(N) original magnet and sampled magnet after grain boundary diffusion
[0111]
[0112] It can be seen from the above test data that when the thermal demagnetization temperature is set lower than the parameter range of the present invention, the remanence of the obtained magnet after grain boundary diffusion is significantly reduced, and the consistency of magnetic properties becomes worse.
[0113] Comparative Example 4
[0114] Compared with Example 1, the difference is that the magnetizing capacitor is 4500 μF and the magnetizing voltage is 2800 V.
[0115] Ten magnets were randomly selected from the magnets after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface. The average surface magnetic intensity (absolute value) of the magnet pole surface were 829Gs, 795Gs, 763Gs, 812Gs, 805Gs, 781Gs, 765Gs, 746Gs, 792Gs, and 813Gs respectively.
[0116] Ten magnets were randomly selected from 200 magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 6 below.
[0117] Table 6. Magnetic properties data of N55(N) original magnet and sampled magnet after grain boundary diffusion
[0118]
[0119] It can be seen from the above test data that compared with the method in Example 1, the magnetizing voltage and capacitance of this comparative example are relatively small, and the consistency of the magnetic properties of the magnet after magnetic adsorption, deposition and diffusion is poor, which cannot meet the more stringent batch consistency requirements.
[0120] Comparative Example 5
[0121] 200 pieces of N55 (N) brand magnets with a size of 25 mm × 12 mm × 4 mm were successively pickled and sandblasted, and the magnets were subjected to unsaturated magnetization using a magnetizer, the magnetizing capacitor was selected to be 2000 μF, the magnetizing voltage was 1000 V, and the magnetizing deflection angle was controlled to be less than 5 degrees, to obtain the magnets to be attached; the magnets to be attached were evenly placed and fixed in a detachable magnet fixture to form a magnet group to be attached. Then, according to the method in Example 1, the magnets were placed in the attachment chamber of the magnetic adsorption deposition equipment and subjected to diffusion heat treatment to obtain the final target diffusion magnet.
[0122] Ten magnets were randomly selected from the magnets after passing through the thermal demagnetization box for surface magnetic distribution test of the magnet pole surface. The average surface magnetic intensity (absolute value) of the magnet pole surface were: 181Gs, 172Gs, 151Gs, 193Gs, 169Gs, 203Gs, 179Gs, 186Gs, 212Gs, and 166Gs, respectively.
[0123] Ten magnets were randomly selected from 200 magnets after grain boundary diffusion for magnetic property testing. The test results of remanence (Br), coercive force (Hcj) and squareness (Hk / Hcj) of the original magnets and the sampled magnets after grain boundary diffusion are shown in Table 7.
[0124] Table 7. Magnetic properties data of N55 (N) original magnet and magnet sampled after grain boundary diffusion
[0125]
[0126] It can be seen from the above test data that, compared with the method in Example 1, the magnetizing voltage and capacitance of this comparative example are further reduced, the magnetic properties of the magnet after magnetic adsorption, deposition and diffusion are poor, and the batch consistency is further reduced.
[0127] In summary, the grain boundary diffusion method of NdFeB magnets deposited by magnetic adsorption in the present invention can effectively improve the magnetic properties; and the magnets are processed by magnetic adsorption deposition equipment to achieve batch production of magnets and meet batch consistency requirements.
[0128] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition, characterized in that: The method for grain boundary diffusion of NdFeB magnets by magnetic adsorption deposition comprises: performing thermal demagnetization after supersaturation magnetization of NdFeB magnets, and then performing diffusion source powder attachment and diffusion heat treatment to obtain NdFeB magnets after grain boundary diffusion.
2. A method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition, characterized in that: The method for grain boundary diffusion of NdFeB magnets by magnetic adsorption deposition comprises: (1) After supersaturation magnetization, the NdFeB magnet is detachably fixed on a detachable magnet fixture to obtain a magnet assembly to be attached; (2) transferring the magnet group to be attached to a magnetic adsorption deposition device, and sequentially performing thermal demagnetization, dust removal and cooling, and adhering the diffusion source powder to the magnet surface through circulating powder raising to obtain the magnet to be diffused; (3) The diffused magnet is subjected to diffusion heat treatment to obtain a NdFeB magnet after grain boundary diffusion.
3. The method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition according to claim 2, characterized in that: The magnetic adsorption deposition equipment comprises a thermal demagnetization box, a dust removal cooling box, an attachment chamber, and a transition chamber which can be closed and connected in sequence. The NdFeB magnet moves in the magnetic adsorption deposition equipment through a transmission group.
4. A magnetic adsorption deposition device, characterized in that: It comprises a thermal demagnetization box, a dust removal cooling box, an attachment chamber and a transition chamber which can be closed and connected in sequence. The NdFeB magnet moves in the magnetic adsorption deposition equipment through a transmission group.
5. The magnetic adsorption deposition device according to claim 4, characterized in that: The attachment chamber comprises an attachment chamber supporting outer box and an attachment chamber rolling inner cavity, and conical tightening ports with a taper of 10 to 45 degrees are arranged at both ends of the attachment chamber rolling inner cavity; a number of inclined attachment chamber inner cavity powder stirring blades are evenly distributed inside the attachment chamber rolling inner cavity; a closable gate of the attachment chamber outer box is arranged on the top of the attachment chamber supporting outer box, and a closable gate of the attachment chamber inner cavity is arranged on the top of the attachment chamber rolling inner cavity, and diffusion source powder enters the attachment chamber rolling inner cavity through the closable gate of the attachment chamber outer box and the closable gate of the attachment chamber inner cavity in turn; the attachment chamber rolling inner cavity is driven by a motor group to rotate the attachment chamber rolling inner cavity to drive the attachment chamber inner cavity powder stirring blades to circulate the diffusion source powder; the linear speed of the bottom edge of the attachment chamber inner cavity powder stirring blades is 0.1 to 5.0 m / s.
6. A method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition, characterized in that: The method comprises: (1) After supersaturation magnetization, the NdFeB magnet is detachably fixed on a detachable magnet fixture to obtain a magnet assembly to be attached; (2) transferring the magnet group to be attached to the magnetic adsorption deposition equipment as described in claim 4, and sequentially performing thermal demagnetization, dust removal and cooling, and adhering the diffusion source powder to the magnet surface through circulating powder raising to obtain the magnet to be diffused; (3) The diffused magnet is subjected to diffusion heat treatment to obtain a NdFeB magnet after grain boundary diffusion.
7. The method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition according to claim 1, 2 or 6, characterized in that: The magnetizing capacitance during the supersaturation magnetization is greater than 4800 μF, and the magnetizing voltage is greater than 3200V.
8. The method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition according to claim 1, 2 or 6, characterized in that: The thermal demagnetization temperature is 260-300° C., and the time is 0.1-30 min. After the thermal demagnetization, the pole surface magnetism of the NdFeB magnet is 800-1100 Gs.
9. The method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition according to claim 1, 2 or 6, characterized in that: The adsorption loading amount of the diffusion source powder on the NdFeB magnet during the diffusion source powder attachment is 1-3 wt % of the mass of the NdFeB magnet after the diffusion source powder is attached.
10. The method for grain boundary diffusion of NdFeB magnets using magnetic adsorption deposition according to claim 1, 2 or 6, characterized in that: Diffusion heat treatment includes two-stage heat treatment, vacuum degree ≤10 -2 Pa; the heating rate of the first stage heat treatment is 0.1-5°C / min, the holding temperature is 880-920°C, and the holding time is 1-12h; cooled to room temperature, and the second stage heat treatment is carried out, the heating rate of the second stage heat treatment is 5-15°C / min, the holding temperature is 460-520°C, and the holding time is 1-12h.
Citation Information
Patent Citations
Preparation method of high-performance permanent magnet and vacuum undulator magnetic structure with high-performance permanent magnet
CN106847494A
Magnetic stabilization method of high-stability permanent magnet material and obtained high-stability permanent magnet material
CN114360849A
Thermal deformation neodymium-iron-boron magnet and preparation method thereof
CN115458319A
Efficient grain boundary diffusion method for neodymium-iron-boron magnet
CN115719673A
Method for identifying irreversible demagnetization of grain boundary diffusion neodymium-iron-boron magnet through magnetic field distribution
CN115728684A